RITUAL MAGI DALAM BUDAYA MASYARAKAT MUSLIM BANTEN - Humaeni Ayatullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2015)
This article discusses various magical rituals and their meaningsfor Muslim society of Banten. How the meanings and functions of rituals; what kinds of magical rituals used and practiced by Muslim society of Banten become two main focuses of this article; besides, it also tries to analyze how Muslim society of Banten understand the various magical rituals. This article is the result of a field research using ethnographical method based on anthropological perspective. To analyze the data, the researcher uses structural-functional approach. Library research, participant-observation, and depth-interview are the methods used to collectthe data. Performing various magical rituals for the practicians of magic in Banten is a very important action that must be conducted by the magicians or someone who learns magical sciences. Magical ritual becomes an important condition for the successfulness of magic. If they do not this, there is a belief that they will fail in obtaining the magical effects. Magical ritual should be also conducted in certain places and certain time withvarious magical formula and magical actions under the supervision of magicians. The use of these magical rituals becomes a portrait of the pragmatical life style of Bantenese society who still believes in magical powers.